ANALISIS KUALITAS LINGKUNGAN SUNGAI WANGI-BEJI, PASURUAN YANG DIDUGA TERCEMARI OLEH LIMBAH PABRIK, PEMUKIMAN DAN PERTANIAN - Moh. Awaludin Adam; Maftuch Maftuch; Yuni Kilawati; Yenny Risjani (Samakia : Jurnal Ilmu Perikanan, 2018)
The aim of study to determine the environmental quality, content and distribution of heavy metals in the waters of the Wangi River, Beji Sub-District, Pasuruan Regency in relation to the interests of environmental conservation around the river. Method of sampling doned by chosen, taking into account the condition of research area, current and depth of research area.The intended to see to what extent pollutant concentrations are spreading. Observation of water quality during research in different seasons of the rainy season (October 2016 to February 2017) and dry season (March to September 2017). Based on the results of environmental quality testing and heavy metals can be concluded that the environmental quality at the Wangi river flow is already at the threshold, so that the required waste prevention and environmental conservation activities. This should get great attention from the public in general and the local government in particular. The hope for the future is pollution of the Wangi River can be avoided and overcome.